Islamic Legal Perspective on the Enforcement of Public Order in Bandar Lampung Regional Regulation on Urban Conduct - Gusti Rahman; Nurnazli Nurnazli; Eko Hidayat (CV. Dyoqu Publishing and Management, 2025)
Background: Local regulations on urban conduct are designed to uphold order and public welfare in Indonesian cities. In Bandar Lampung, however, the practical application of such regulations reveals persistent enforcement gaps. Aims: This research seeks to evaluate how effectively public order norms are implemented by municipal authorities in Bandar Lampung and to explore the compatibility of these enforcement practices with Islamic legal doctrines. Method: The study uses a qualitative fieldwork approach involving interviews with civil enforcement officers, observations of regulatory practices, and analysis of local policy documents. It draws on the Islamic legal framework, particularly the concepts of executive authority (Sulṭah Tanfiẓiyyah) and moral oversight (Sulṭah Muraqabah), to contextualize the findings. Result: The results indicate a disconnect between legal mandates and on-the-ground enforcement. While regulations exist, their implementation tends to be informal, lacking firm action or systemic follow-up. Resource limitations and public unawareness further complicate consistent enforcement. Conclusion: The study underscores the need for institutional strengthening and civic education to foster a culture of compliance. Embedding Islamic legal ethics into enforcement practices may also contribute to more balanced and morally grounded public order governance.